Stacked battery
Patent Information
- Application Number
- CN202610954863.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-09-15
Smart Images

Figure CN122762852A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of lithium batteries, and more specifically to stacked batteries. Background Technology
[0002] Lithium-ion batteries have advantages such as high energy density, long cycle life, and environmental friendliness, and are widely used in various electronic products. In order to improve the volumetric energy density of lithium-ion batteries, stacked batteries have gradually abandoned the outermost negative electrode structure and adopted a single-sided coated electrode structure for the outermost positive electrode. This reduces one negative electrode layer and two separator layers, thereby freeing up more space for the positive electrode active material and helping to improve the energy density of the battery.
[0003] However, the single-sided coating of the outermost layer of a stacked battery has the following problems: First, the uncoated foil side of the positive current collector, lacking active material coating, does not generate any stress. Second, the coated surface with active material will exert an adhesive force on the surface of the positive current collector, causing the single-sided coated electrode to bend towards the foil side (i.e., the uncoated side). This bending phenomenon poses a significant challenge during manufacturing, easily leading to angled plates during stacking, hot pressing, and other processes, thereby increasing the risk of battery short circuits and severely impacting the production yield and manufacturing efficiency of stacked batteries. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned problems existing in the prior art and to provide a stacked battery. The outermost first positive electrode of the stacked battery provided by this invention releases the edge stress of the single-sided coating layer, improves the curling of the first positive electrode, ensures that the electrode does not bend during the stacking process, reduces the short circuit risk of the stacked battery, and improves the safety performance of the battery.
[0005] To achieve the above objectives, the first aspect of the present invention provides a stacked battery, the stacked battery comprising a positive electrode, a separator, and a negative electrode stacked together; The positive electrode includes two first positive electrode plates and multiple second positive electrode plates. The first positive electrode plates are located on both sides of the cell stacking direction, and the second positive electrode plates are located between the two first positive electrode plates. The second positive electrode includes a positive current collector and second positive active material layers located on opposite sides of the thickness direction of the positive current collector; The negative electrode sheet includes a negative electrode current collector and negative electrode active material layers disposed on opposite sides of the negative electrode current collector in the thickness direction; The first positive electrode includes a positive current collector and a first positive active material layer disposed on one side surface of the positive current collector; Fourier transform infrared spectroscopy analysis revealed that the first positive electrode active material layer possesses at least one of the following characteristic peaks: Fourier transform infrared spectroscopy analysis revealed that the positive electrode active material layer possesses at least one of the following characteristic peaks: At 1080cm -1 Up to 1180cm -1 CN stretching vibration peaks appeared within the range; At 3300cm -1 Up to 3600cm -1 NH stretching vibration peaks appeared within the range; At 1000cm -1 Up to 1100cm -1 An S=O vibrational absorption peak appears within the range; At 1450cm -1 Up to 1600cm -1 The stretching vibration peak of the benzene ring structure appears within the range.
[0006] The present invention, by adopting the above technical solution, has the following beneficial effects: The outermost first positive electrode of the stacked battery has a first positive electrode active material layer coated on one side. Infrared spectroscopy reveals at least one of the aforementioned characteristic peaks in this first active material layer, indicating that the polar solvent and fluorinated binder within the first active material layer have undergone chemical bonding and reconstruction, forming a stress-relieving network. This releases the edge stress of the single-sided coating layer and effectively improves electrode curling. Therefore, it effectively avoids corner bending and short-circuit problems caused by electrode curling during the stacking process, significantly improving the manufacturing yield and safety performance of the stacked battery.
[0007] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values close to those ranges or values. For numerical ranges, endpoint values of various ranges, endpoint values of various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In this document, unless otherwise specified, data ranges include endpoints. Attached Figure Description
[0008] Figure 1 The diagram shows an example and a schematic diagram of the structure of a stacked battery in the prior art.
[0009] Figure 2 The diagram shown is a structural schematic of an example of an adhesive application method.
[0010] Wherein, 1-first adhesive tape; 2-second adhesive tape; 3-third adhesive tape; 4-fourth adhesive tape. Detailed Implementation
[0011] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0012] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0013] This invention provides a stacked battery, the stacked battery comprising a cell, the cell comprising a positive electrode, a separator, and a negative electrode stacked together; The positive electrode includes two first positive electrode plates and multiple second positive electrode plates. The first positive electrode plates are located on both sides of the cell stacking direction, and the second positive electrode plates are located between the two first positive electrode plates. The second positive electrode includes a positive current collector and second positive active material layers located on opposite sides of the thickness direction of the positive current collector; The negative electrode sheet includes a negative electrode current collector and negative electrode active material layers disposed on opposite sides of the negative electrode current collector in the thickness direction; The first positive electrode includes a positive current collector and a first positive active material layer disposed on one side surface of the positive current collector; Fourier transform infrared spectroscopy analysis revealed that the first positive electrode active material layer possesses at least one of the following characteristic peaks: Fourier transform infrared spectroscopy analysis revealed that the positive electrode active material layer possesses at least one of the following characteristic peaks: At 1080cm -1 Up to 1180cm -1 CN stretching vibration peaks appeared within the range; At 3300cm -1 Up to 3600cm -1 NH stretching vibration peaks appeared within the range; At 1000cm -1 Up to 1100cm -1 An S=O vibrational absorption peak appears within the range; At 1450cm -1 Up to 1600cm -1 The stretching vibration peak of the benzene ring structure appears within the range.
[0014] In this invention, the two first positive electrode sheets located on the outermost layer of the battery are single-sided coated electrodes, with the first positive electrode active material layer only on one side of the positive electrode current collector. This layer-reduction design directly reduces the use of one negative electrode sheet and two separator layers, freeing up more space for the first positive electrode active material, thereby increasing the volumetric energy density of the battery. After the first positive electrode active material is coated and dried, the single-sided coated first positive electrode sheet undergoes a secondary coating treatment with the aforementioned specific polar solvent. Therefore, the CN, NH stretching vibration peaks, S=O vibration absorption peaks, or benzene ring structure stretching vibration peaks detected in the infrared spectrum of the first positive electrode sheet belong to pyrrolidone, sulfoxide, or benzene ring polar solvents. By performing a secondary coating treatment with polar solvents on the first positive electrode sheet, the binder in the first positive electrode active material layer and the polar solvent rebuild intermolecular forces and chemical bonds, releasing the edge stress of the positive electrode active material layer, which can significantly improve the curling of the first positive electrode sheet and effectively improve the manufacturing efficiency and safety performance of the stacked battery.
[0015] Figure 1 The diagram shows a schematic of a cell in a stacked battery in an example and in the prior art. In the prior art, in a conventional cell structure ( Figure 1 As shown on the left side of the middle section), the outermost single-sided coated positive electrode sheet severely curls towards the foil surface due to the adhesive stress between the coated surface and the current collector. The improved cell structure provided by this invention addresses this curling issue. Figure 1 (As shown on the right side of the middle section), after the first positive electrode is treated with a second coating of polar solvent, the electrode is restored to flatness.
[0016] In some embodiments, the first positive electrode active material layer includes a fluorinated binder, which includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-trifluorochloroethylene copolymer.
[0017] In some embodiments, based on the mass of the first positive electrode active material layer, the mass percentage of the fluorinated binder is 0.1%-5%, for example, it can be 0.1%, 0.3%, 0.5%, 0.7%, 1%, 2%, 3%, 4%, 5%, or any value within the range of any two of the above values. When the fluorinated binder content is set within this range, it can ensure the basic adhesion between the first positive electrode active material layer and the positive electrode current collector, and also achieve effective stress release after secondary treatment with polar solvent. If the fluorinated binder content is less than 0.1%, the adhesion of the first positive electrode active material layer is too weak, the positive electrode slurry coating is difficult, and the stress release effect after treatment with polar solvent solution is limited, and the first positive electrode sheet may still curl; if it is higher than 5%, the fluorinated binder content is high, the inner layer treatment is insufficient, the effect on edge stress release is poor, and the effect of improving curling is not good.
[0018] The binder content test method in the first positive electrode active material is as follows: scrape out the positive electrode powder from the first positive electrode sheet, put it in a vacuum oven at 100℃ and bake it for 24 hours to fully dry the moisture. Then put the positive electrode powder into a thermogravimetric analyzer, introduce high-purity nitrogen gas, and heat it at a rate of 10℃ / min. There is a binder thermogravimetric decomposition peak of 0.1% to 5% between 400 and 600℃.
[0019] The present invention also provides a method for preparing the first positive electrode, comprising the following steps: A slurry containing a positive electrode active material is coated onto the surface of the positive electrode current collector to form a first positive electrode active material layer. A polar solvent is coated onto the surface of the first positive electrode active material layer to obtain the first positive electrode sheet.
[0020] After the polar solvent is coated onto the first positive electrode active material layer, it penetrates into the cured layer and interacts with the fluorinated binder. This interaction disrupts the existing chemical bonds and intermolecular forces between the binder molecular chains and between the binder and the positive electrode active material particles and current collector, causing localized movement and rearrangement of the binder molecular chains. Subsequently, as the polar solvent gradually evaporates or is dried, the fluorinated binder re-establishes a new, more evenly distributed bonding network on the surface of the positive electrode current collector and between the first positive electrode active material particles. This releases the edge stress caused by single-sided coating, restoring the first positive electrode sheet from a state of severe curling towards the foil surface to a flat or nearly flat state.
[0021] In some embodiments, the mass fraction of the polar solvent is 1% to 50%.
[0022] In some embodiments, the mass fraction of the polar solvent can be adjusted by dissolving it in an alcohol solution. Alcohol solvents include, but are not limited to, ethanol, methanol, propanol, and isopropanol.
[0023] In some embodiments, coating a polar solvent onto the surface of the first positive electrode active material layer specifically includes: passing the positive electrode sheet coated with the first positive electrode active material layer through a coating machine, where a coating die sprays a polar solvent onto the surface of the first positive electrode active material layer, with a coating flow rate of 10 mL / min-30 mL / min, a coating speed of 15 m / min-50 m / min, a drying time of 1 min-5 min, an oven wind speed of 10 m / s-25 m / s, an oven temperature of 100℃-130℃, and then obtaining the first positive electrode sheet after roll forming and die cutting.
[0024] In some embodiments, the polar solvent includes one or a combination of pyrrolidone solvents, sulfoxide solvents, and benzene ring solvents. Pyrrolidone solvents include, but are not limited to, N-methylpyrrolidone (NMP), 2-pyrrolidone, 3-pyrrolidone, 4-pyrrolidone, and γ-valerone; sulfoxide solvents include, but are not limited to, thionyl chloride, dimethyl sulfoxide, and diphenyl sulfoxide; and benzene ring solvents include, but are not limited to, benzene, toluene, ethylbenzene, and xylene.
[0025] In some embodiments, the porosity of the first positive electrode is 35%-45%, for example, it can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or any value within the range of any two of the above values. Here, "porosity" refers to the percentage of the pore volume inside the active material layer of the positive electrode to the apparent volume of the electrode. If the porosity of the first positive electrode is too low (e.g., below 35%), the interior of the positive electrode active material layer is too dense, making it difficult for polar solvents to fully penetrate into the coating layer. This results in insufficient contact with the fluorinated binder, preventing effective activation of the binder and comprehensive bond reconstruction, leading to incomplete stress release and poor improvement in electrode curling. Controlling the porosity within the range of 35%-45% provides sufficient channels for the penetration and diffusion of polar solvents, ensuring sufficient contact between the solvent and the binder inside the coating layer. This promotes comprehensive reconstruction of the bonding network and effective stress release, ultimately achieving a significant improvement in the flatness of the first positive electrode from curling.
[0026] The method for determining the porosity of the positive electrode includes: cutting a certain area from the first positive electrode, measuring the length and width of the electrode with a ruler, measuring the thickness of the electrode with a micrometer, and calculating the electrode volume; the apparent volume of the electrode = the measured thickness of the electrode. Electrode length Electrode width; The cut positive electrode is placed into the sample chamber of a fully automated true density analyzer, and the sample chamber is filled with inert helium gas. Then, it is expanded into another expansion chamber of known volume. The true volume of the sample can be calculated using the pressure before and after gas diffusion. Porosity = (apparent electrode volume - true electrode volume) / apparent electrode volume 100%.
[0027] In some embodiments, the compaction density of the first positive electrode sheet is less than or equal to the compaction density of the second positive electrode sheet. "Compaction density" refers to the mass per unit volume of the positive electrode sheet after rolling. Due to the secondary coating process with polar solvents, the positive active material layer of the first positive electrode sheet acquires a more relaxed structure, and its compaction density is naturally lower than that of an untreated single-sided electrode sheet. Controlling its compaction density to not exceed that of the second positive electrode sheet avoids the problem of discontinuity in the electronic conductivity network caused by excessive structural relaxation, and also avoids the loss of porosity and wettability advantages gained from the treatment due to excessive compaction.
[0028] In some embodiments, the compaction density of the second positive electrode is 3.2 g / cc to 3.5 g / cc.
[0029] The compaction density test method is to calculate it by combining the electrode surface density with the electrode thickness measured by a micrometer. The electrode surface density can be measured by cutting out a 1cm piece. 2 The weight of the positive electrode sheet is W1. The weight of the positive electrode current collector is W2 after the positive electrode active material layer is scraped off. Then the surface density is (W1-W2) / 1.
[0030] In some embodiments, the areal density of the first positive electrode is 4 mg / cm³. 2 -15mg / cm 2 For example, it can be 4mg / cm 2 5mg / cm 2 6mg / cm 2 7mg / cm 2 8mg / cm 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 13mg / cm 2 14mg / cm 2 15mg / cm 2 Or any value within the range formed by any two of the above values. "Area density" refers to the mass of the positive electrode active material layer per unit area. When the area density of the first positive electrode sheet is less than 4 mg / cm³... 2 When the positive electrode active material layer is too thin, although polar solvents can easily penetrate it, the overall mechanical strength of the first positive electrode sheet is weak. There is still a risk of deformation or breakage during subsequent processing, transport, and stacking. Furthermore, the low active material loading makes it difficult to construct high-energy-density batteries. When the areal density is greater than 15 mg / cm³... 2 If the positive electrode active material layer is too thick, the fluorinated binder deep in the positive electrode active material layer (near the interface of the positive electrode current collector) may not be able to achieve sufficient solvation during polar solvent treatment. This results in incomplete release of edge stress in the inner layer, causing the first positive electrode sheet to have a smooth surface but residual stress inside, which may cause curling to reappear during subsequent cycles or hot pressing.
[0031] The areal density of the first positive electrode can be obtained by conventional methods in the art, such as the weighing method.
[0032] In some embodiments, the first positive electrode active material layer includes a first positive electrode active material; the first positive electrode active material includes at least one of lithium cobalt oxide, ternary materials, and lithium iron phosphate.
[0033] Specifically, lithium cobalt oxide (such as LiCoO2) has a high compaction density and a stable voltage platform. Its layered structure is compatible with fluorinated binders and polar solvents. The reconstructed bonding network can uniformly cover the surface of the positive electrode active material, releasing stress while maintaining the electron and ion transport pathways during the charging and discharging process.
[0034] The chemical formula of the ternary material is Li a Ni x Co y Mn z O2, where 0.9≤a≤1.1, 0.5≤x≤0.65, 0<y≤0.2, 0<z≤0.3. Ternary materials exhibit high chemical stability to electrolytes and polar solvents, and their high specific capacity helps to improve the energy density of batteries.
[0035] Lithium iron phosphate (LiFePO4) has excellent thermal stability and cycle life. Its olivine structure is also compatible with the processing method in this invention, which can release curling stress while maintaining good safety characteristics of the electrode.
[0036] In some embodiments, the cell body has two opposing sidewalls extending along the height direction; each sidewall is provided with a first adhesive tape, a second adhesive tape, and a third adhesive tape along the height direction of the cell; the first adhesive tape is positioned near the top of the cell, with a gap between the first adhesive tape and the top of the cell; the third adhesive tape is positioned near the bottom of the cell, with a gap between the third adhesive tape and the bottom of the cell; the second adhesive tape is positioned between the first and third adhesive tapes; a fourth adhesive tape is provided on the bottom surface of the cell body, the fourth adhesive tape not completely covering the bottom surface of the cell body. This method of attaching seven adhesive tapes (top, middle, and bottom) applies a uniform clamping force to the stacked cores from multiple directions including top, bottom, left, right, and bottom, forcibly constraining the outermost first positive electrode sheet and preventing it from undergoing new displacement, warping, or even bending during battery transport or due to equipment vibration.
[0037] In some embodiments, the total coverage width of the first, second, and third adhesive strips on the same sidewall is 1 / 5 to 1 / 3 of the height of the stacked battery body. If the total coverage width is too low, i.e., less than 1 / 5 of the height, the binding force provided by the adhesive strips is insufficient, and the outermost electrode may locally bulge or deform in the gaps between the adhesive strips during battery electrolyte filling. If the total coverage width is too high, i.e., greater than 1 / 3 of the height, the non-adhesive area is too small, and the electrolyte cannot smoothly penetrate into the internal layers of the battery from the gaps, severely deteriorating the electrolyte wetting effect and easily causing interface lithium plating.
[0038] In some embodiments, the width of the fourth adhesive tape is 1 / 18 to 1 / 5 of the width of the stacked battery body. Controlling the adhesive width within this range prevents the bottom from becoming loose while maintaining a sufficiently wide open channel for electrolyte to seep in from the bottom core. When the adhesive width exceeds 1 / 5 of the total width, the bottom wetting resistance increases significantly, leading to excessive polarization during battery formation; when the adhesive width is less than 1 / 18, it is prone to forming loose adhesion or detachment at the bottom, making it impossible to effectively limit the position of the rolled-up electrode sheets.
[0039] In some implementations, such as Figure 2 As shown, the stacked battery has a non-full-coverage fixing structure with seven adhesive strips, formed by setting three layers of adhesive strips (first adhesive strip 1, second adhesive strip 2, and third adhesive strip 3) on each of the left and right sides, and a fourth adhesive strip (fourth adhesive strip 4) in the center of the bottom edge. The first adhesive strip is 1-3mm from the top of the stacked core, the third adhesive strip is 1-3mm from the bottom of the stacked core, and the second adhesive strip is in the center. The total coverage width of the three strips on the side wall is 1 / 5 to 1 / 3 of the height of the stacked core; the width of the bottom adhesive strip is 1 / 18 to 1 / 5 of the width of the stacked core.
[0040] In some embodiments, the adhesive paper is selected from at least one of polyester adhesive paper and polyimide adhesive paper.
[0041] In some embodiments, the number of positive electrode sheets is equal to the number of negative electrode sheets. In this case, the stacking sequence can be: outermost single-sided coated positive electrode sheet (first positive electrode sheet) - separator - double-sided coated negative electrode sheet - separator - double-sided coated positive electrode sheet (second positive electrode sheet) - ... - separator - double-sided coated negative electrode sheet - separator - outermost single-sided coated positive electrode sheet (first positive electrode sheet). Compared to the traditional structure where the outermost layer is a negative electrode sheet and the number of positive electrode sheets is less than the number of negative electrode sheets, this configuration where the number of positive electrode sheets equals the number of negative electrode sheets eliminates the need for the outermost purely mechanically protective negative electrode sheet and the two separator layers separating it from the positive electrode. The saved space is used to fill the positive electrode active material, which helps to improve the overall volumetric energy density of the battery. In this structure, since the problem of curling of the outermost single-sided positive electrode sheet has been solved, the battery can maintain a compact stacked state in the thickness direction. The interlayer gap will not increase or local stress concentration will not be caused by the bending of the electrode sheet, so that the stacked battery has both high volumetric energy density and excellent manufacturing reliability.
[0042] In some embodiments, the areal density of the negative electrode is 1 mg / cm³. 2 -10mg / cm 2 For example, it can be 1 mg / cm³ 2 2mg / cm 2 3mg / cm 2 4mg / cm 2 5mg / cm 2 6mg / cm2 7mg / cm 2 8mg / cm 2 9mg / cm 2 10mg / cm 2 Or any value within the range formed by any two of the above points.
[0043] The stacked battery provided by this invention has a flat first electrode sheet on the outermost layer of the internal cell, which makes it less prone to corner bending and internal short circuit defects during hot pressing, packaging and other processes. As a result, the battery exhibits high production yield and consistent safety performance.
[0044] In some embodiments, the stacked battery further includes an electrolyte, and the contact angle between the first positive electrode and the electrolyte is 27°-40°.
[0045] The "contact angle" refers to the angle at the solid-liquid-gas three-phase interface formed by electrolyte droplets on the surface of the positive electrode, used to characterize the wettability of the electrolyte on the electrode. Untreated single-sided coated positive electrodes often have contact angles greater than 40° due to the presence of a large amount of hydrophobic fluorinated binder-rich phase and low porosity on their surface. After treatment with polar solvents, the surface distribution and molecular chain conformation of the fluorinated binder change, increasing the exposure of polar groups. Simultaneously, the increased porosity of the first positive electrode also increases its surface roughness (enhancing hydrophilicity). These factors work synergistically, allowing electrolyte droplets to spread more rapidly and fully on the electrode surface, effectively reducing interfacial impedance, promoting rapid lithium-ion transport within the electrode, and improving the battery's rate performance and cycle stability.
[0046] The contact angle testing method involves: applying electrolyte to the surface of the positive electrode using a clean dropper, and then immediately stopping any vibration or movement. Based on the three-phase interface formed by the water droplet, the water droplet angle is measured using a water droplet angle meter.
[0047] In some embodiments, the electrolyte comprises a chain-like carboxylic acid ester, which accounts for 10%-30% of the total mass of the electrolyte. For example, it can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, or any value within the range of any two of the above values. If its content is less than 10%, the effect on reducing electrolyte viscosity and improving wettability is weak; if its content is greater than 30%, it may lead to a decrease in the overall dielectric constant of the electrolyte, affecting the degree of lithium salt dissociation, and may exacerbate the oxidative decomposition of the electrolyte due to the relatively poor stability of the chain-like carboxylic acid ester on the positive electrode surface, thereby reducing the cycle life of the battery.
[0048] In some embodiments, the chain carboxylic esters include dimethyl carbonate (DMC), diethyl carbonate (DEC), or ethyl methyl carbonate (EMC), etc., which are solvents with low viscosity and good low-temperature flow properties. Introducing the above-mentioned chain carboxylic esters into the electrolyte can reduce the viscosity of the entire electrolyte system and improve the kinetic performance of the battery.
[0049] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0050] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0051] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0052] The lithium-ion batteries in the following examples and comparative examples were all prepared according to the following methods.
[0053] Example 1a 1. Preparation of positive electrode sheet (1) Preparation of the positive electrode active material layer: The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2, conductive carbon black (Super-P), carbon nanotubes, and fluorinated binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:1:2. N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred at high speed to obtain a positive electrode slurry with a solid content of 68%.
[0054] (2) Preparation of double-sided positive electrode: The above slurry was uniformly coated on both sides of the aluminum foil current collector (thickness 12μm), and after drying and rolling, a double-sided positive electrode was obtained, denoted as P1. Its compaction density was 3.4g / cc.
[0055] (3) Preparation of single-sided positive electrode and polar solvent treatment: The above slurry was uniformly coated on one side of an aluminum foil current collector (12 μm thick), and after drying and rolling, a single-sided positive electrode was obtained, denoted as P2. Its single-sided coating surface density was 10 mg / cm³. 2The compacted density was 3.1 g / cc, and the porosity before treatment was approximately 22%. The single-sided positive electrode P2 was fed into a coating machine, where an anhydrous ethanol solution of γ-valerone (a polar solvent belonging to the pyrrolidone class) was sprayed onto the coating surface using a coating die. The mass fraction of γ-valerone in this solution was 30%. The coating flow rate was 20 mL / min, the coating speed was 30 m / min, and after coating, the electrode was dried in a 40 m long oven with hot air at a temperature of 115℃, an air velocity of 18 m / s, and a drying time of 3 min. After drying, the electrode was rolled to adjust the compacted density to 3.1 g / cc, and then die-cut to obtain a single-sided positive electrode with improved curling, designated P3.
[0056] Fourier transform infrared spectroscopy analysis revealed that the positive electrode active material layer of P3 was at 1080 cm⁻¹. -1 Up to 1180cm -1 CN stretching vibration peaks appear within the range, at 3300 cm⁻¹. -1 Up to 3600cm -1 NH stretching vibration peaks appear within the range, at 1000 cm⁻¹. -1 Up to 1100cm -1 An S=O vibrational absorption peak appears within the range.
[0057] Physical properties of P3 were tested, revealing a porosity of 40%. The contact angle between P3 and the subsequent electrolyte was 33°. Thermogravimetric analysis showed that the fluorinated binder (PVDF) in the positive electrode active material layer of P3 comprised approximately 2% by mass.
[0058] 2. Preparation of negative electrode sheet Artificial graphite, conductive agent Super-P, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 95:1.5:1.5:2, using deionized water as a solvent, and stirred at high speed to obtain a negative electrode slurry with a solid content of 50%. This slurry was uniformly coated on both sides of a copper foil current collector (8 μm thick), and after drying and rolling, a negative electrode sheet, denoted as N1, was obtained with an areal density of 5 mg / cm³. 2 .
[0059] 3. Electrolyte preparation In an argon-filled glove box, lithium hexafluorophosphate (LiPF6) was dissolved in a non-aqueous solvent to obtain an electrolyte with a LiPF6 concentration of 1 mol / L. The non-aqueous solvent consisted of 35% ethylene carbonate (EC), 5% propylene carbonate (PC), 40% dimethyl carbonate (DMC), and 20% ethyl propionate (EP).
[0060] 4. The diaphragm is a 16μm thick polypropylene / polyethylene / polypropylene three-layer composite diaphragm.
[0061] 5. Battery assembly The positive electrode plates P1, P3 and the negative electrode plate N1 are punched into a specified size, and a Z-type stacking machine is used for stacking. The stacking sequence is: P3-separator-N1-separator-P1-separator-N1-……-N1-separator-P1-separator-N1-separator-P3. A cell body in which the total number of positive electrode plates is equal to the total number of negative electrode plates is thus formed.
[0062] Taping and fixing: a first adhesive tape (upper), a second adhesive tape (middle) and a third adhesive tape (lower) are respectively arranged on the left side wall and the right side wall of the cell body. The upper adhesive tape is 2mm away from the top of the stacked core, the lower adhesive tape is 2mm away from the bottom of the stacked core, and the middle adhesive tape is located at the middle position of the side wall. On the same side wall, the total covering width of the first, second and third adhesive tapes is 1 / 4 of the height of the stacked core. A fourth adhesive tape is arranged in the center of the bottom surface of the cell body, and the width thereof is 1 / 9 of the width of the stacked core. The adhesive tape used is polyimide adhesive tape with a thickness of 30μm.
[0063] The taped bare stacked core is encapsulated with an aluminum plastic film, the above electrolyte is injected, after being baked in vacuum at a high temperature of 85°C for 24 hours, formation and aging are performed to obtain a stacked battery.
[0064] Test Example (1) Battery short-circuit rate test: the bare stacked cores prepared in the examples and comparative examples are subjected to a short-circuit test on a voltage withstand tester at 200V for 5s, and the short-circuit rate data of the stacked cores in each group of solutions are recorded.
[0065] (2) Battery cycle test: according to a 5C / 10C charge-discharge regime, a cycle test is performed on the batteries prepared in the examples and comparative examples at a high temperature of 45°C, the voltage range is 4.3V~3V, and the number of cycles when the battery capacity decays to 80% of the initial capacity is recorded. During the cycle, the battery is disassembled to determine the curling condition of the outermost positive electrode plate.
[0066] (3) Test method for curling condition: the disassembled outermost positive electrode plate is flatly placed on a glass platform, and a ruler is used to measure the height H of the highest curling point. H≤1mm means no curling; 1mm<H≤3mm means slight curling; 3mm<H≤5mm means relatively slight curling; H>5mm means severe curling.
[0067] The procedure is carried out with reference to Example 1a, and the main differences of the remaining examples are shown in Table 1 below, which are specifically as follows: Example Group 1 changes the type of polar solvent; Example Group 2 changes the content of fluorine-containing binder; Example Group 3 adjusts the mass fraction of polar solvent to change the contact angle between the first positive electrode plate and the electrolyte; Example Group 4 adjusts the mass fraction of polar solvent, coating speed and drying wind speed in coordination to change the porosity of the first positive electrode plate. Comparative Example 1 does not perform any polar solvent treatment; Comparative Example 2 uses pure absolute ethanol of n-hexane (i.e., non-polar solvent) for treatment.
[0068] In Comparative Example 1, the outermost positive electrode sheet was severely curled, and the stacked short circuit rate was 86%; in Comparative Example 2, the outermost positive electrode sheet was severely curled, and the stacked short circuit rate was 86%.
[0069] Table 1 As shown in Table 1 above, the present invention performs polar solvent coating treatment on the first positive electrode sheet coated on the outermost single side of the stacked battery, so that the fluorinated binder in the first positive electrode active material layer undergoes chemical bonding and reconstruction with the polar solvent to form a stress relief network, thereby effectively releasing the edge stress of the single-sided coating layer, effectively improving electrode curling, and significantly reducing the short circuit risk of the stacked battery.
[0070] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Furthermore, it should be noted that the scope of the methods and apparatuses in the embodiments of this application is not limited to performing functions in the order shown or discussed, but may also include performing functions substantially simultaneously or in the reverse order, depending on the functions involved. For example, the described methods may be performed in a different order than described, and various steps may be added, omitted, or combined. Additionally, features described with reference to certain examples may be combined in other examples.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A stacked battery, characterized by, The stacked battery includes a cell, and the cell includes a positive electrode, a separator, and a negative electrode stacked together. The positive electrode includes two first positive electrode plates and multiple second positive electrode plates. The first positive electrode plates are located on both sides of the cell stacking direction, and the second positive electrode plates are located between the two first positive electrode plates. The second positive electrode includes a positive current collector and a second positive active material layer located on opposite sides of the thickness direction of the positive current collector; The negative electrode sheet includes a negative electrode current collector and negative electrode active material layers disposed on opposite sides of the negative electrode current collector in the thickness direction; The first positive electrode sheet includes a positive current collector and a first positive active material layer disposed on one side surface of the positive current collector; Fourier transform infrared spectroscopy analysis revealed that the first positive electrode active material layer possesses at least one of the following characteristic peaks: The C-N stretching vibration peak appears in the range of 1080 cm -1 to 1180 cm -1 ; N-H stretching vibration peak appears in the range of 3300 cm -1 to 3600 cm -1 -1. S=O vibration absorption peaks appear in the range of 1000 cm -1 to 1100 cm -1 -1. S=O vibration absorption peaks appear in the range of 1000 cm to 1100 cm The benzene ring structure stretching vibration peak appears in the range of 1450 cm -1 to 1600 cm -1 -1.
2. The stacked battery of claim 1, wherein The first positive electrode active material layer includes a fluorinated binder; Preferably, based on the mass of the first positive electrode active material layer, the mass percentage of the fluorinated binder is 0.1%-5%; Preferably, the fluorinated binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-trifluorochloroethylene copolymer.
3. The stacked battery of claim 1, wherein The porosity of the first positive electrode is 35%-45%.
4. The stacked battery of claim 1, wherein The compaction density of the first positive electrode is less than or equal to the compaction density of the second positive electrode.
5. The stacked battery of claim 1, wherein The areal density of the first positive electrode sheet is 4 mg / cm 2 - 15 mg / cm 2 .
6. The stacked cell of any one of claims 1-5, wherein, The first positive electrode active material layer includes a first positive electrode active material; Preferably, the first positive electrode active material includes at least one of lithium cobalt oxide, ternary materials, and lithium iron phosphate.
7. The stacked cell of any one of claims 1-5, wherein, The battery cell body has two opposing sidewalls extending along the height direction; a first adhesive strip, a second adhesive strip, and a third adhesive strip are respectively provided on each sidewall along the height direction of the battery cell; the first adhesive strip is located near the top of the battery cell, and a gap is left between the first adhesive strip and the top of the battery cell; the third adhesive strip is located near the bottom of the battery cell, and a gap is left between the third adhesive strip and the bottom of the battery cell; the second adhesive strip is located between the first adhesive strip and the third adhesive strip; a fourth adhesive strip is provided on the bottom surface of the battery cell body, and the fourth adhesive strip does not completely cover the bottom surface of the battery cell body.
8. The stacked battery of claim 7, wherein, On the same side wall, the total coverage width of the first adhesive tape, the second adhesive tape, and the third adhesive tape is 1 / 5 to 1 / 3 of the height of the stacked battery body. Preferably, the width of the fourth adhesive tape is 1 / 18 to 1 / 5 of the width of the stacked battery body.
9. The stacked battery of any one of claims 1-5, wherein, The number of positive electrode plates is equal to the number of negative electrode plates; Preferably, the face density of the negative electrode sheet is 1 mg / cm 2 - 10 mg / cm 2 .
10. The stacked battery of any one of claims 1-5, wherein, It also includes an electrolyte, and the contact angle between the first positive electrode and the electrolyte is 27°-40°; Preferably, the electrolyte comprises a chain-like carboxylic acid ester, which accounts for 10%-30% of the total mass of the electrolyte.